Hubungan Dukungan Suami dalam Pemberian ASI eksklusif, Literature Review - Dwija Sistha Aprilia Firdaus; I Gusti Ayu Karnasih; Dian Aby Restanty (ARTERI : Jurnal Ilmu Kesehatan, 2022)
According to Basic Health Research in 2014-2018, the achievement of exclusive breastfeeding in East Java is still below the target set by the Ministry of Health of the Republic of Indonesia. The lack of exclusive breastfeeding given by the mother can be caused by so many factors, one of them is the lack of support that mothers get from their environment, especially from their husband. This study was held to determine the correlation of husband's support in exclusive breastfeeding. Articles were collected through Google and PubMed using “Father’s role and exclusive breastfeeding”, and “Husband’s role in exclusive breastfeeding” as the keywords. Screening towards the articles was based on PEOS frameworks, which consist of 2 international articles and 7 national articles. From those articles, 4 articles have been accredited by SCOPUS, ISI, and ARJUNA. The analysis showed that there is a significant correlation of husband support in exclusive breastfeeding. Husband's support can give a significant effect on exclusive breastfeeding. From the analysis that has been done, 66.7% of the journal articles stated that there is a relationship between husband's support in exclusive breastfeeding, and the rest of them (33.3%) stated that there is no relationship between husband's support in exclusive breastfeeding.